Memórias narradas na educação escolar indígena dos Kariri-Xocó/AL - Santos, Taysa Kawanny Ferreira (2018)
The aim of this research was to analyze the memories narrated in didactic supports elaborated by the Kariri-Xocó Indians, from Alagoas. In order to do this, it was necessary to conceptualize “memories” in the field of history and of indigenous thinking; identify the narrated and propagated memories in Kariri-Xocó’s teaching supports and understand the meanings of the memories propagated in the didactic supports for differentiated and intercultural Indigenous School Education. Our study was guided by the approach of qualitative research in Education and was based on the assumptions of hermeneutical phenomenology because it aimed to evidence the meanings ascribed by the subjects to the researched phenomenon. It was a case study in which we adopted an ethnographic research posture, with the intention of value the listening, the observation and the respect to cultural practice. The research was developed with the Kariri-Xocó people, who lives in the indigenous territory of Porto Real do Colégio, east of Alagoas, 180 kilometers far from the capital Maceió. By investigating the narrated and propagated memories in the didactic support made by Kariri-Xocó indians, it was evidenced that the meanings ascribed to the memories were related to the history collectively produced in the way of “being and living Kariri-Xocó”. Therefore, we observed in the analyzed narratives that the registered memories correspond to three important aspects of the Kariri-Xocó’s lives: the memories of origin, the memories of being and living and the memories of living together. Among the memories of origin lie the narratives about their ancestry, their cosmology, their history and their recent memory. In the memories of being and living, by the words of the elders and of the youngest, we found the narratives about the way the Kariri-Xocó live in recent times related to a past of abundance. This present contains a complaint of the precariousness of life by the denial of indigenous rights. In the memories of living together, the narratives point to relationships among themselves, and with other human being and not human. The research also pointed to the participation of indigenous teachers and leaders as agents, involved in and with the school in the protagonism to effect a differentiated and intercultural Indigenous School Education.